Water-based silicon-carbon negative electrode binder for lithium battery as well as preparation and application of water-based silicon-carbon negative electrode binder
By modifying the aqueous silicon-carbon negative electrode binder and using the copolymerization technology of multiple monomers, the problem of volume expansion of the silicon-based negative electrode material of lithium-ion batteries during circulation is solved, and the cycle stability and electrical performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411671272.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-21
AI Technical Summary
The silicon-based anode material of existing lithium-ion batteries expands severely during the circulation process, resulting in the pulverization of the electrode structure and the rapid attenuation of capacity, limiting its practical application.
By modifying the aqueous silicon carbon negative electrode binder, copolymerization is carried out using suitable ratios of hydrophilic monomers, hydrophobic monomers and functional monomers to form a binder capable of forming a variety of intermolecular forces with the surface of silicon particles, and the volume expansion of the silicon negative electrode material is inhibited.
The cycling stability and electrical performance of the silicon-based negative electrode material is significantly improved, the expansion rate of the electrode plate is reduced, the bonding force with the current collector is enhanced, and the battery's room temperature cycle performance and charge and discharge rate performance are improved.
Smart Images

Figure CN119662167A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer and lithium battery materials, and specifically relates to an aqueous silicon-carbon negative electrode binder for lithium batteries and its preparation and application. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in 3C, electric vehicles and other fields. With the trend of high nickel content in positive electrode ternary materials, the importance of improving the quality and specific capacity of negative electrode materials is increasing day by day. At present, the specific capacity of graphite negative electrode products of mainstream manufacturers is above 350mAh / g, which is close to the theoretical upper limit of specific capacity of 372mAh / g. It is time to find new negative electrode materials with higher specific capacity.
[0003] Silicon has a theoretical specific capacity of up to 4200mAh / g, which is more than 10 times that of graphite materials. It can provide channels for lithium ion insertion and extraction from all directions and has excellent fast charging performance. Therefore, high-energy-density silicon-based negative electrode materials have become the direction of future development. However, during the cycle, the volume of silicon microparticles (SiMP) will expand dramatically (>300%), resulting in structural crushing of the electrode material and rapid capacity decay, which limits the practical application of silicon-based negative electrodes. Currently, only a small amount of silicon-based negative electrode materials are usually added to graphite for use.
[0004] Since polyacrylic acid (PAA) contains a large number of carboxyl groups, PAA may interact with the hydroxyl groups on the surface of SiMP in three ways: 1) hydrogen bonding; 2) partial esterification; 3) complete esterification. Therefore, a strong interaction is formed between the two, which is beneficial to overcome the volume expansion of SiMP and improve the cycle stability. However, ordinary PAA binders have limited inhibitory effects on the volume expansion of SiMP, and have limited adhesion to negative electrode materials and negative electrode sheets, so they have limited effect on improving the electrical properties of negative electrode sheets. Summary of the invention
[0005] The primary purpose of the present invention is to provide an aqueous silicon-carbon negative electrode binder for lithium batteries, modify PAA, and suppress the volume expansion of silicon negative electrode materials by optimizing the binder structure to obtain a PAA derivative binder with better performance.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned aqueous silicon-carbon negative electrode binder.
[0007] Another object of the present invention is to provide an application of the above-mentioned aqueous silicon-carbon negative electrode binder in the preparation of silicon-carbon negative electrode sheets for lithium-ion batteries.
[0008] The purpose of the present invention is achieved through the following technical solutions:
[0009] A water-based silicon-carbon negative electrode binder for lithium batteries is obtained by copolymerizing monomers having the following mass percentage ratios: 30% to 50% of a hydrophilic monomer, 20% to 40% of a hydrophobic monomer, and 10% to 30% of a functional monomer; the hydrophilic monomer is an unsaturated monomer containing carboxylic acid, amide, and sulfonic acid groups; the hydrophobic monomer is at least one of acrylonitrile, methacrylonitrile, acrylate, and methacrylate; and the functional monomer is at least one of vinyl polysiloxane, sodium allyl sulfonate, sodium methallyl sulfonate, sodium p-styrene sulfonate, and N-vinyl pyrrolidone.
[0010] Further preferably, the hydrophilic monomer is at least one of acrylic acid, methacrylic acid, acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N-hydroxyethyl acrylamide, vinyl sulfonic acid, propylene sulfonic acid, and methacryl sulfonic acid; more preferably, it is a combination of acrylic acid or methacrylic acid and at least one of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N-hydroxyethyl acrylamide, vinyl sulfonic acid, propylene sulfonic acid, and methacryl sulfonic acid.
[0011] Further preferably, the hydrophobic monomer is a combination of acrylonitrile or methacrylonitrile and acrylate or methacrylate; more preferably, a combination of acrylonitrile or methacrylonitrile and at least one of ethyl acrylate, n-butyl acrylate, hydroxyethyl acrylate, isooctyl acrylate, and hydroxypropyl acrylate.
[0012] More preferably, the functional monomer is a combination of vinyl polysiloxane and at least one of sodium allyl sulfonate, sodium methyl allyl sulfonate, sodium p-styrene sulfonate and N-vinyl pyrrolidone.
[0013] More preferably, the vinyl polysiloxane has a number average molecular weight in the range of 1000 to 20000 g / mol, and the vinyl group (-CH 2 ) terminal group and / or side chain vinyl polysiloxane with a content of 0.25 to 6 wt%.
[0014] The present invention adds vinyl polysiloxane as a functional monomer, which can better form more intermolecular forces with silicon particles on the surface of silicon-based negative electrode materials than other functional monomers, thereby achieving a better silicon particle dispersion effect; and the low surface tension property of the polysiloxane segment can improve the wetting ability of the binder, and enhance the binding force between the silicon particles and the current collector through the above-mentioned effect; at the same time, the low expansion rate characteristics of polysiloxane and the multi-vinyl cross-linking to improve the cohesive force characteristics can better inhibit the volume expansion of silicon negative electrode materials and improve the cycle performance. However, the low surface tension characteristics of the polysiloxane functional monomer lead to poor compatibility with other monomers and poor modification effect. By combining with sulfonates and pyrrolidone monomers with certain surface activity, the defect of poor compatibility of polysiloxane can be improved, thereby improving the mixing and copolymerization effects of vinyl polysiloxane and improving the modification performance.
[0015] A method for preparing the above-mentioned aqueous silicon-carbon negative electrode binder comprises the following preparation steps:
[0016] (1) adding a hydrophilic monomer, a hydrophobic monomer, a functional monomer, a first batch of initiators, other additive regulators and deionized water into a reaction kettle and stirring them uniformly, and then introducing nitrogen to form a monomer emulsion;
[0017] (2) The monomer emulsion of step (1) is heated to 60-80° C., and then a second batch of initiator is added to keep the temperature for reaction. After the reaction is completed, the emulsion is cooled, diluted and neutralized to obtain a water-based silicon-carbon negative electrode binder.
[0018] Furthermore, the initiator includes a peroxide initiator and / or a reducing agent initiator.
[0019] Preferably, the peroxide initiator is one or more of sodium persulfate, ammonium persulfate, potassium persulfate, benzoyl peroxide, tert-butyl hydroperoxide, and diisopropylbenzene hydroperoxide.
[0020] Preferably, the reducing agent initiator is one or more of sodium sulfite, sodium bisulfite, sodium pyrosulfite, isoascorbic acid, and sodium hypophosphite.
[0021] Furthermore, the other additive regulator is one or more of alkyl diphenyl ether disulfonate, higher alcohol sulfate ester salt, aliphatic sulfonate, alkyl benzene sulfonate, aliphatic carboxylate, lithium hydroxide monohydrate, sodium hydroxide solution, potassium hydroxide solution, ammonia water, and triethylamine.
[0022] Furthermore, the total amount of deionized water used is 100% to 400% of the total mass of the reaction monomers.
[0023] The application of the above-mentioned aqueous silicon-carbon negative electrode binder in the preparation of silicon-carbon negative electrode sheets for lithium-ion batteries.
[0024] Furthermore, the application method is: adding the silicon-carbon composite negative electrode active material and the conductive agent and the aqueous silicon-carbon negative electrode binder according to any one of claims 1 to 4 into an aqueous solvent, mixing, stirring and grinding to prepare a negative electrode slurry, coating it on the negative electrode collector, and then drying, compacting, and punching to obtain a lithium-ion battery silicon-carbon negative electrode sheet.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] (1) The aqueous silicon-carbon negative electrode binder of the present invention uses hydrophilic monomers containing carboxylic acid, amide, and sulfonic acid groups as main raw materials, which are widely available and easy to obtain. By copolymerizing with hydrophobic monomers and specific functional monomers in a suitable ratio, more intermolecular forces can be formed with silicon particles on the surface of silicon-based negative electrode materials during the preparation of the electrode sheet to enhance the binding force with the current collector. At the same time, a self-healing effect can also be produced during the expansion of the silicon-based negative electrode sheet to inhibit the volume expansion of the silicon negative electrode material and improve the cycle performance of the silicon-based negative electrode material.
[0027] (2) The present invention provides a water-based silicon-carbon negative electrode binder for lithium batteries. In the process of modifying and synthesizing PAA, a binder with both soft and hard segments and better performance is obtained, which combines the negative electrode conductive material and the current collector well and has good dispersion and wetting ability. At the same time, various polar groups on the entire molecular chain, such as carboxyl, hydroxyl, amino, sulfonic acid, etc., can improve the binding force with the silicon-carbon material through intermolecular hydrogen bonds and through the flexibility and compatibility of the polysiloxane chain, thereby enhancing the cohesive force between the active substances and the peeling force between the electrode sheets.
[0028] (3) The preparation method of the water-based silicon-carbon negative electrode binder of the present invention adopts emulsion polymerization, which is relatively simple and reduces the cost of synthesizing the binder. It does not produce "three wastes" and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a graph showing the thickness measurement results of the negative electrode sheet prepared with the aqueous silicon-carbon negative electrode binder of Example 1 after 200 cycles.
[0030] Figure 2 Schematic diagram of the peeling force test of the negative electrode sheet in the embodiment.
[0031] Figure 3 This is a graph showing the cycle test results of batteries prepared with the aqueous silicon-carbon negative electrode binder of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0033] Example 1
[0034] The aqueous silicon-carbon negative electrode binder of this embodiment is prepared by the following method:
[0035] (1) By weight percentage, 30% acrylic acid and 15% acrylamide are added to a hydrophilic monomer, 30% acrylonitrile and 5% n-butyl acrylate are added to a reactor to form a monomer emulsion. The total amount of deionized water is 300% of the total weight of the monomers.
[0036] (2) Add the second batch of initiators sodium persulfate and sodium bisulfite into water and dissolve them evenly to obtain an initiator solution (sodium persulfate is 0.16% of the total mass of the monomer, and sodium bisulfite is 0.08% of the total mass of the monomer). Heat the monomer emulsion of step (1) to 60°C, add the initiator solution to the monomer emulsion in batches, first add 1 / 2 of the initiator solution and keep warm for 2 hours; continue to heat to 70°C and add 1 / 4 of the initiator solution to react for 1 hour; then cool to 50°C and continue to add the remaining 1 / 4 of the initiator solution to react for 1 hour. After the reaction is completed, cool and dilute to a solid content of 10% and neutralize to obtain a water-based silicon-carbon negative electrode binder.
[0037] Example 2
[0038] (1) By weight percentage, 35% acrylic acid and 10% acrylamide are added to the hydrophilic monomers, 25% acrylonitrile and 10% isooctyl acrylate are added to the hydrophobic monomers, 10% vinyl polysiloxane (vinyl-terminated polysiloxane with an average molecular weight of 1000 g / mol and a vinyl content of 5.5%) and 10% N-vinyl pyrrolidone are added to the reactor, the mixture is stirred evenly, and then nitrogen is introduced to form a monomer emulsion. The total amount of deionized water is 300% of the total weight of the monomers.
[0039] Step (2) is the same as in Example 1.
[0040] Example 3
[0041] (1) Add 30% acrylic acid and 10% N-hydroxymethyl acrylamide as hydrophilic monomers, 25% acrylonitrile and 15% ethyl acrylate as hydrophobic monomers, 5% vinyl polysiloxane (terminated vinyl polysiloxane with an average molecular weight of 20,000 g / mol and a vinyl content of 0.25%) as functional monomers, 15% sodium p-styrene sulfonate, the first batch of initiator sodium persulfate (0.16% relative to the total weight of the monomers), other additive regulator sodium dodecyl sulfate (0.4% relative to the total weight of the monomers) and deionized water into a reactor, stir evenly, and then introduce nitrogen to form a monomer emulsion. The total amount of deionized water used is 300% of the total weight of the reaction monomers.
[0042] Step (2) is the same as in Example 1.
[0043] Example 4
[0044] (1) Add hydrophilic monomers 30% methacrylic acid and 15% acrylamide, hydrophobic monomers 25% acrylonitrile and 10% hydroxypropyl acrylate, functional monomers 10% sodium allyl sulfonate and 10% sodium p-styrene sulfonate, the first batch of initiator sodium persulfate (0.16% relative to the total weight of monomers), other additive regulator sodium dodecyl sulfate (0.4% relative to the total weight of monomers) and deionized water into a reactor and stir evenly, then introduce nitrogen to form a monomer emulsion. The total amount of deionized water used is 300% of the total weight of the reaction monomers.
[0045] Step (2) is the same as in Example 1.
[0046] Example 5
[0047] (1) Add 30% methacrylic acid and 10% propylene sulfonic acid as hydrophilic monomers, 30% methacrylonitrile and 10% n-butyl acrylate as hydrophobic monomers, 5% sodium methyl allyl sulfonate and 15% sodium p-styrene sulfonate as functional monomers, the first batch of initiator sodium persulfate (0.16% relative to the total weight of monomers), other additive regulator sodium dodecyl sulfate (0.4% relative to the total weight of monomers) and deionized water into a reactor and stir evenly, then introduce nitrogen to form a monomer emulsion. The total amount of deionized water used is 300% of the total weight of the reaction monomers.
[0048] Step (2) is the same as in Example 1.
[0049] Example 6
[0050] (1) Add 30% methacrylic acid and 15% methacrylic acid as hydrophilic monomers, 25% acrylonitrile and 10% isooctyl acrylate as hydrophobic monomers, 5% vinyl polysiloxane (side-chain vinyl polysiloxane with an average molecular weight of 4000 g / mol and a vinyl content of 4.5%) as functional monomers, 15% sodium methallyl sulfonate, the first batch of initiator sodium persulfate (0.16% relative to the total weight of the monomers), other additive regulator sodium dodecyl sulfate (0.4% relative to the total weight of the monomers) and deionized water into a reactor, stir evenly, and then introduce nitrogen to form a monomer emulsion. The total amount of deionized water used is 300% of the total weight of the reaction monomers.
[0051] Step (2) is the same as in Example 1.
[0052] Example 7
[0053] (1) By weight percentage, 30% acrylic acid and 20% acrylamide as hydrophilic monomers, 25% acrylonitrile and 5% n-butyl acrylate as hydrophobic monomers, 10% vinyl polysiloxane (side-chain vinyl polysiloxane with an average molecular weight of 2000 g / mol and a vinyl content of 5.2%) as functional monomers, 10% sodium p-styrene sulfonate, the first batch of initiator sodium persulfate (0.16% relative to the total weight of the monomers), other additive regulator sodium dodecyl sulfate (0.4% relative to the total weight of the monomers) and deionized water are added to a reaction kettle and stirred evenly, and then nitrogen is introduced to form a monomer emulsion. The total amount of deionized water used is 300% of the total weight of the reaction monomers.
[0054] Step (2) is the same as in Example 1.
[0055] Example 8
[0056] (1) By weight percentage, 20% acrylic acid and 10% acrylamide are added to a hydrophilic monomer, 30% acrylonitrile and 10% n-butyl acrylate are added to a reactor to form a monomer emulsion. The total amount of deionized water is 300% of the total weight of the monomers.
[0057] Step (2) is the same as in Example 1.
[0058] Example 9
[0059] The aqueous silicon-carbon negative electrode binder of this embodiment is prepared by the following method:
[0060] (1) By weight percentage, 30% acrylic acid and 20% acrylamide as hydrophilic monomers, 15% acrylonitrile and 5% n-butyl acrylate as hydrophobic monomers, 20% vinyl polysiloxane (terminated vinyl polysiloxane with an average molecular weight of 8000 g / mol and a vinyl content of 0.7%) as functional monomers, 10% sodium p-styrene sulfonate, the first batch of initiator sodium persulfate (0.16% relative to the total weight of the monomers), other additive regulator sodium dodecyl sulfate (0.4% relative to the total weight of the monomers) and deionized water are added to a reactor and stirred evenly, and then nitrogen is introduced to form a monomer emulsion. The total amount of deionized water used is 300% of the total weight of the reaction monomers.
[0061] Step (2) is the same as in Example 1.
[0062] Example 10
[0063] The aqueous silicon-carbon negative electrode binder of this embodiment is prepared by the following method:
[0064] (1) By weight percentage, 45% acrylic acid as a hydrophilic monomer, 30% acrylonitrile as a hydrophobic monomer, 5% n-butyl acrylate, 10% vinyl polysiloxane as a functional monomer (end vinyl polysiloxane with an average molecular weight of 3000 g / mol and a vinyl content of 6%), 10% sodium p-styrene sulfonate, the first batch of initiator sodium persulfate (0.16% relative to the total weight of the monomers), other additive regulator sodium dodecyl sulfate (0.4% relative to the total weight of the monomers) and deionized water are added to a reaction kettle and stirred evenly, and then nitrogen is introduced to form a monomer emulsion. The total amount of deionized water used is 300% of the total weight of the reaction monomers.
[0065] Step (2) is the same as in Example 1.
[0066] Embodiment 11
[0067] The aqueous silicon-carbon negative electrode binder of this embodiment is prepared by the following method:
[0068] (1) By weight percentage, 30% acrylic acid and 15% acrylamide as hydrophilic monomers, 35% acrylonitrile as hydrophobic monomers, 10% vinyl polysiloxane (end vinyl polysiloxane with an average molecular weight of 6000 g / mol and a vinyl content of 4.8%) as functional monomers, 10% sodium p-styrene sulfonate, the first batch of initiator sodium persulfate (0.16% relative to the total weight of the monomers), other additive regulator sodium dodecyl sulfate (0.4% relative to the total weight of the monomers) and deionized water are added to a reaction kettle and stirred evenly, and then nitrogen is introduced to form a monomer emulsion. The total amount of deionized water used is 300% of the total weight of the reaction monomers.
[0069] Step (2) is the same as in Example 1.
[0070] Example 12
[0071] The aqueous silicon-carbon negative electrode binder of this embodiment is prepared by the following method:
[0072] (1) By weight percentage, 30% acrylic acid and 15% acrylamide are added to the hydrophilic monomers, 30% acrylonitrile and 5% n-butyl acrylate are added to the hydrophilic monomers, 20% vinyl polysiloxane (end vinyl polysiloxane with an average molecular weight of 15000 g / mol and a vinyl content of 3.6%) is added to the functional monomers, the first batch of initiator sodium persulfate (0.16% relative to the total weight of the monomers), the other additive regulator sodium dodecyl sulfate (0.4% relative to the total weight of the monomers) and deionized water are added to the reaction kettle, stirred evenly, and then nitrogen is introduced to form a monomer emulsion. The total amount of deionized water used is 300% of the total weight of the reaction monomers.
[0073] Step (2) is the same as in Example 1.
[0074] Comparative Example 1
[0075] The aqueous silicon-carbon negative electrode binder of this embodiment is prepared by the following method:
[0076] (1) By weight percentage, 40% acrylic acid and 15% acrylamide are added to the hydrophilic monomers, 40% acrylonitrile and 5% n-butyl acrylate are added to the reactor as the first batch of initiator sodium persulfate (0.16% relative to the total weight of the monomers), other additive regulator sodium dodecyl sulfate (0.4% relative to the total weight of the monomers) and deionized water are stirred evenly, and then nitrogen is introduced to form a monomer emulsion. The total amount of deionized water used is 300% of the total weight of the reaction monomers.
[0077] Step (2) is the same as in Example 1.
[0078] The monomer compositions of the binders of the above embodiments and comparative examples are shown in Table 1 below:
[0079] Table 1
[0080]
[0081]
[0082] Comparative Example 2
[0083] A negative electrode binder of this comparative example is a mixture of carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) emulsion, wherein the ratio of CMC to SBR is 1:1 (solid ratio).
[0084] The performance of the negative electrode sheets and lithium-ion batteries prepared with the binders obtained in the above examples and comparative examples were tested:
[0085] 1) The preparation method of the negative electrode sheet for testing is as follows: using water as a solvent, 0.95 parts by weight of a silicon-carbon composite material (gram capacity 550 mAh / g) as a negative electrode active material, 0.14 parts by weight of a conductive agent (conductive carbon black Super P), 0.06 parts by weight of carbon nanotubes and 0.03 parts by weight of the silicon-carbon negative electrode binder prepared in the above embodiments and comparative examples (the parts are calculated based on solid content) are mixed, stirred and ground to prepare a negative electrode slurry, and after adjusting the solid content of the slurry to 50%, it is evenly coated on a copper foil, and then dried, compacted, and punched to prepare a negative electrode sheet.
[0086] 2) The preparation method of the test lithium-ion battery is as follows: the obtained negative electrode plate is vacuum dried at 110°C for 24 hours, and then placed in a glove box with a dry argon atmosphere, and a button cell is assembled using a metal lithium sheet as the counter electrode; the diaphragm is a microporous membrane of polyolefin, and the electrolyte is the company's commercialized electrolyte for silicon-based negative electrode lithium-ion batteries.
[0087] 3) The negative electrode sheets prepared in Examples 1 to 14 and Comparative Examples 1 to 2 and the assembled button cells were used to measure the electrode sheet expansion rate (the electrode sheet expansion rate was measured by the electrode sheet thickness measurement method, and the electrode sheet thickness change before and after 200 cycles was measured using a SEM microscope. The thickness measurement results of the negative electrode sheet prepared by the aqueous silicon-carbon negative electrode binder in Example 1 after 200 cycles are as follows Figure 1 As shown) and peeling force performance test (Using a universal tensile tester to perform a 180° peeling force test, the peeling force test uses a sample made of 2 cm wide and longer than 5 cm, so the unit of the peeling force curve is N / cm 2 , the corresponding test diagram is as follows Figure 2 The test results are shown in Table 2 below.
[0088] Table 2
[0089] Serial number Binder Pole expansion rate (%) <![CDATA[Peeling force (N / cm 2 )]]> 1 Example 1 22 0.214 2 Example 2 26 0.201 3 Example 3 28 0.194 4 Example 4 30 0.173 5 Example 5 31 0.168 6 Example 6 27 0.197 7 Example 7 25 0.210 8 Example 8 20 0.202 9 Example 9 21 0.197 10 Example 10 31 0.165 11 Embodiment 11 32 0.166 12 Example 12 26 0.166 13 Example 13 27 0.169 14 Embodiment 14 29 0.171 15 Comparative Example 1 31 0.145 16 Comparative Example 2 35 0.124
[0090] It can be seen from the results of Examples 1 to 14 and Comparative Example 2 in Table 2 that the aqueous silicon-carbon negative electrode binder of the present invention can significantly reduce the expansion rate of the pole piece and improve the peeling force compared with conventional CMC and SBR binders. It can be seen from the comparison results of Example 9 with Examples 10 to 11 that the functional monomer does not contain vinyl polysiloxane, the pole piece expansion rate of the obtained binder is significantly improved and the peeling force is reduced to a certain extent, indicating that the addition of vinyl polysiloxane functional monomer has a very significant effect on reducing the expansion rate of the pole piece and can improve the bonding performance to a certain extent. It can be seen from the comparison results of Example 1 with Examples 12 to 13 that the combination of hydrophilic monomers using acrylic acid and the combination of hydrophobic monomers using acrylonitrile can significantly improve the pole piece peeling strength compared with pure acrylic acid and acrylonitrile, and also have a certain effect on reducing the expansion rate of the pole piece. By comparing the results of Example 1 with Example 14, it can be seen that the combination of functional monomers using vinyl polysiloxane can significantly reduce the expansion rate of the pole piece and improve the peeling force compared with simple vinyl polysiloxane. The reason is that sodium methyl allyl sulfonate, sodium p-styrene sulfonate or N-vinyl pyrrolidone can significantly improve the compatibility of vinyl polysiloxane in the reaction system, thereby improving the polymerization effect and improving the overall performance. By comparing the results of Example 1 with Comparative Example 1, it can be seen that the addition of functional monomers has a very significant effect on reducing the expansion rate of the pole piece and improving the peeling force.
[0091] 4) The button-type batteries assembled in Examples 1 to 14 and Comparative Examples 1 to 2 were used to perform a room temperature cycle performance test. The test results are shown in Table 3 below. The button-type battery cycle test results assembled in Example 1 and Comparative Example 1 are shown in Table 3. Figure 3 shown.
[0092] Table 3
[0093]
[0094] It can be seen from the comparison results of Examples 1 to 14 and Comparative Example 2 in Table 3 that the use of the aqueous silicon-carbon negative electrode binder of the present invention can significantly improve the room temperature cycle performance of the battery compared with conventional CMC and SBR binders. It can be seen from the comparison results of Example 1 and Comparative Example 1 that the addition of functional monomers has a very significant effect on improving the room temperature cycle performance. It can be seen from the comparison results of Example 1 and Examples 12 to 14 that the combination of hydrophilic monomers using acrylic acid or methacrylic acid, the combination of hydrophobic monomers using acrylonitrile or methacrylonitrile, and the combination of functional monomers using vinyl polysiloxane can achieve better room temperature cycle performance.
[0095] 5) The button cells assembled in Examples 1 to 14 and Comparative Examples 1 to 2 were used to perform charge and discharge rate performance tests. The test results are shown in Table 4 below.
[0096] Table 4
[0097]
[0098] From the comparison results of Examples 1 to 14 and Comparative Example 2 in Table 4, it can be seen that the use of the aqueous silicon-carbon negative electrode binder of the present invention can significantly improve the charge and discharge rate performance of the battery compared with conventional CMC and SBR binders. From the comparison results of Example 1 and Comparative Example 1, it can be seen that the addition of functional monomers has a very significant effect on improving the charge and discharge rate performance. From the comparison results of Example 1 and Examples 12 to 14, it can be seen that the combination of hydrophilic monomers using acrylic acid or methacrylic acid, the combination of hydrophobic monomers using acrylonitrile or methacrylonitrile, and the combination of functional monomers using vinyl polysiloxane can achieve better charge and discharge rate performance.
[0099] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A water-based silicon-carbon negative electrode binder for lithium batteries, characterized in that: The invention is obtained by copolymerizing monomers having the following mass percentage ratios: 30% to 50% of a hydrophilic monomer, 20% to 40% of a hydrophobic monomer, and 10% to 30% of a functional monomer; the hydrophilic monomer is an unsaturated monomer containing carboxylic acid, amide, and sulfonic acid groups; the hydrophobic monomer is at least one of acrylonitrile, methacrylonitrile, acrylate, and methacrylate; and the functional monomer is at least one of vinyl polysiloxane, sodium allyl sulfonate, sodium methallyl sulfonate, sodium p-styrene sulfonate, and N-vinyl pyrrolidone.
2. The aqueous silicon-carbon negative electrode binder for lithium batteries according to claim 1, characterized in that: The hydrophilic monomer is at least one of acrylic acid, methacrylic acid, acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N-hydroxyethyl acrylamide, vinyl sulfonic acid, propylene sulfonic acid, and methacrylic acid.
3. The aqueous silicon-carbon negative electrode binder for lithium batteries according to claim 2, characterized in that: The hydrophilic monomer is a combination of acrylic acid or methacrylic acid and at least one of acrylamide, methacrylamide, N-hydroxymethyl acrylamide, N-hydroxyethyl acrylamide, vinyl sulfonic acid, propylene sulfonic acid, and methacrylic acid.
4. The aqueous silicon-carbon negative electrode binder for lithium batteries according to claim 1, characterized in that: The hydrophobic monomer is a combination of acrylonitrile or methacrylonitrile and acrylate or methacrylate.
5. The aqueous silicon-carbon negative electrode binder for lithium batteries according to claim 4, characterized in that: The hydrophobic monomer is a combination of acrylonitrile or methacrylonitrile and at least one of ethyl acrylate, n-butyl acrylate, hydroxyethyl acrylate, isooctyl acrylate and hydroxypropyl acrylate.
6. The aqueous silicon-carbon negative electrode binder for lithium batteries according to claim 1, characterized in that: The functional monomer is a combination of vinyl polysiloxane and at least one of sodium allyl sulfonate, sodium methyl allyl sulfonate, sodium p-styrene sulfonate and N-vinyl pyrrolidone.
7. The aqueous silicon-carbon negative electrode binder for lithium batteries according to claim 6, characterized in that: The vinyl polysiloxane is a terminal and / or side chain vinyl polysiloxane with a number average molecular weight ranging from 1000 to 20000 g / mol and a vinyl content of 0.25 to 6 wt%.
8. A method for preparing an aqueous silicon-carbon negative electrode binder as claimed in any one of claims 1 to 7, characterized in that: The method comprises the following preparation steps: (1) adding a hydrophilic monomer, a hydrophobic monomer, a functional monomer, a first batch of initiators, other additive regulators and deionized water into a reaction kettle and stirring them uniformly, and then introducing nitrogen to form a monomer emulsion; (2) The monomer emulsion of step (1) is heated to 60-80° C., and then a second batch of initiator is added to keep the temperature for reaction. After the reaction is completed, the emulsion is cooled, diluted and neutralized to obtain a water-based silicon-carbon negative electrode binder.
9. The method for preparing an aqueous silicon-carbon negative electrode binder according to claim 8, characterized in that: The first batch of initiators or the second batch of initiators adopts a peroxide initiator or a redox initiator; the peroxide initiator is at least one of sodium persulfate, ammonium persulfate, potassium persulfate, benzoyl peroxide, tert-butyl hydroperoxide, and diisopropylbenzene hydroperoxide; the redox initiator includes an oxidant and a reductant, the oxidant is at least one of sodium persulfate, ammonium persulfate, potassium persulfate, benzoyl peroxide, tert-butyl hydroperoxide, and diisopropylbenzene hydroperoxide, and the reductant is one or more of sodium sulfite, sodium bisulfite, sodium pyrosulfite, isoascorbic acid, and sodium hypophosphite.
10. The method for preparing an aqueous silicon-carbon negative electrode binder according to claim 8, characterized in that: The other additive regulators are one or more of alkyl diphenyl ether disulfonate, higher alcohol sulfate ester salt, aliphatic sulfonate, alkyl benzene sulfonate, aliphatic carboxylate, lithium hydroxide monohydrate, sodium hydroxide solution, potassium hydroxide solution, ammonia water, and triethylamine; the total amount of deionized water used is 100% to 400% of the total mass of the reaction monomers.
11. Use of an aqueous silicon-carbon negative electrode binder according to any one of claims 1 to 7 in the preparation of silicon-carbon negative electrode sheets for lithium-ion batteries.
12. The use of an aqueous silicon-carbon negative electrode binder according to claim 11 in the preparation of a silicon-carbon negative electrode sheet for a lithium-ion battery, characterized in that: The application method is: adding the silicon-carbon composite negative electrode active material, the conductive agent and the aqueous silicon-carbon negative electrode binder according to any one of claims 1 to 7 into an aqueous solvent, mixing, stirring and grinding to prepare a negative electrode slurry, coating the negative electrode slurry on the negative electrode collector, and then drying, compacting and punching to obtain a lithium-ion battery silicon-carbon negative electrode sheet.
Citation Information
Cited By
Negative electrode binder as well as preparation method and application thereof
CN121652736A
A negative electrode binder, a method for preparing the same, and an application thereof
CN121652736B